Production of light aromatics from biomass components co-pyrolyzed with polyethylene via non-thermal plasma synergistic upgrading. (15th February 2023) - Fan, Yongsheng; Lu, Dongsheng; Han, Yue; Yang, Jiaheng; Qian, Cheng; Li, Binyu
Abstract: Catalytic co-pyrolysis of cellulose, xylan and lignin with polyethylene (PE) was conducted using a tandem vacuum pyrolysis and non-thermal plasma (NTP) synergistic upgrading system. HZSM-5, Ti and Ni modified HZSM-5 were employed. Cellulose-derived furfural was difficult to be converted, and increased PE ratio generated more olefins and promoted furfural deoxygenation. Ti-modification raised MAHs from 12.23% to 42.55% while Ni-modification further increased MAHs to 44.36%. However, Ti-modification raised the catalytic coke from 0.12% to 3.20% while Ni-modification mainly increased thermal coke from 1.69% to 4.63%. Xylan co-pyrolyzed with more PE promoted the production of olefins due to reverse Diels-Alder reaction. Ti-modification slightly improved MAHs from 17.09% to 22.58%, while Ni-modification remarkably increased MAHs to 40.90%. Correspondingly, Ti-modification slightly increased light and thermal cokes, while Ni-modification raised all types and total coke content increased from 5.50% to 10.97%. Lignin obtained the lowest oil yield of 15.02% with the maximum MAHs of 84.34%, and co-pyrolysis with PE improved the deoxygenation. Ti-modification increased petroleum-like alkanes with the reduction of MAHs and olefins while Ni-modification increased MAHs from 59.22% to 71.93%. However, the lower oxygen content and more aliphatic branches contributed to the higher ratio of aliphatic hydrogen, and catalysts were coked seriously. Highlights: A tandem vacuum pyrolysis and plasma synergistic upgrading system was used. Diels-Alder reaction was suppressed by plasma, affecting aromatics formation. Ti-modified zeolite as well as plasma synergy enhanced deoxygenation cracking. Ni-modified zeolite improved aromatization, generating more aromatics. Modifications weakened zeolite stability and lignin involvement was the worst.